PENERAPAN TAGUCHI DALAM OPTIMASI PARAMETER UNTUK PERBAIKAN PRODUK FACIAL WASH - Faula Arina; Ahmad Bahauddin; Anggie Maurdi (Jurnal Matematika Sains dan Teknologi, 2022)
PT X is a company engaged in the cosmetic sector. The product with the biggest defect is the green tea tree oil facial wash. This study aims to reduce the number of defects by determining the optimal level setting on the product. The Taguchi method is one of the methods in the experimental design that can be used to control product quality from noise by minimizing variations. This research method uses Taguchi because this method combines experimental results through optimal factors and factor levels and at the same time reduces the number of experiments so as to save time and costs. The experimental factors are water, Nacl, cocamide DEA, citrid acid, mixing speed, mixing time and mixing temperature. The results of this study found that the dominant type of defect in the green tea tree oil facial wash products was the product with low viscosity. In this case, we used a nominal-is-best quality characteristic with a target of 37500 cPs. We found that the optimal setting for green tea tree oil facial wash products were 64.3% of water, 2% of cocamide DEA, 0.3% citric acid and 60 minutes for the mixing period.